(untitled) (Orfeu, 2017)
This paper presents a reflection on sound experimentation and possible paradoxes between music, sound and language in contemporary artistic production, from the appropriation of new digital technologies. From the moment that an acoustic instrument is connected to an interface capable of processing its signal, we have access to the intrinsic potentialities of the sound. Combining investigative processes that can perform the exchange of data and/ or signals between the acoustic instruments, electronic devices/circuits, mobile computers, controllers, smartphones, wireless communication networks, sensors, amplified objects, etc., experimentation with mobile digital devices has opened up an irreversible rift in sound making, greatly expanding artistic possibilities. Sound experimentation, its creation and diffusion are increasingly close to the skin, touch, and are increasingly close to the human body itself. By expanding the focus beyond the traditional approaches on rhythm, melody and harmony, which are linked to a certain period of Western music, and engaging on enhanced and deep listening experiences, we realize the potential that sound carries, with all its expressive nuances. Thus, the appropriation of new technologies enables the creation of a specific type of performance and composition anchored in sound manipulation and a more detailed listening experience that may be dissociated from a specific referentiality.